2019
DOI: 10.1523/jneurosci.0642-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Mutations inTSC2Lead to Abnormalities Associated with Cortical Tubers in Human iPSC-Derived Neurons

Abstract: Tuberous sclerosis complex (TSC) is a genetic disorder caused by mutations in TSC1 or TSC2. Patients frequently have epilepsy, autism spectrum disorder, and/or intellectual disability, as well as other systemic manifestations. In this study, we differentiated human induced pluripotent stem cells (iPSCs) from a female patient with TSC with one or two mutations in TSC2 into neurons using induced expression of NGN2 to examine neuronal dysregulation associated with the neurological symptoms in TSC. Using this meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 51 publications
10
99
0
Order By: Relevance
“…This can explain the patterns of network disorganisation that we observe, manifest as a high number of random and uncorrelated spikes. Furthermore a large reduction in the number of SBs detected in the TSC2 model was associated with an increase in the burst length, consistent with previous reports in both animal and human models [16,40]. Our pharmacological pro ling demonstrated that consistent with that already shown in control human iPSC-derived neurons and in rodent neurons, glutamate and GABA signalling are the primary drivers for the network activity in TSC2 neurons [27].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This can explain the patterns of network disorganisation that we observe, manifest as a high number of random and uncorrelated spikes. Furthermore a large reduction in the number of SBs detected in the TSC2 model was associated with an increase in the burst length, consistent with previous reports in both animal and human models [16,40]. Our pharmacological pro ling demonstrated that consistent with that already shown in control human iPSC-derived neurons and in rodent neurons, glutamate and GABA signalling are the primary drivers for the network activity in TSC2 neurons [27].…”
Section: Discussionsupporting
confidence: 91%
“…We showed that TSC2-derived neurons have common neuronal defects caused by both autosomal dominant TSC1 and TSC2 mutations and that neuronal hyperexcitability of TSC patient-derived cells was reversed by rapamycin [17]. A subsequent study used induced expression NGN2 to generate excitatory neurons from TSC2 +/-, TSC2 -/and TSC2 +/+ cells and replicated the observations on TSC neurons hyperexcitability [16].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…More recently, Winden et al confirmed the increased activity levels of human TSC2−/− neurons by MEA, showing also a difference between control and heterozygous networks. Hypersynchronous neuronal discharges were also found in both TSC2+/− and TSC2−/− neurons [48].…”
Section: Tuberous Sclerosis-tsc1 and Tsc2mentioning
confidence: 85%